Exploring the “Multiple-Hit Hypothesis” of Neurodegenerative Disease: Bacterial Infection Comes Up to Bat - Patrick, Kristin L.; Bell, Samantha L.; Weindel, Chi G.; Watson, Robert O. (Frontiers in Cellular and Infection Microbiology, 2019)
Despite major strides in personalized genomics, it remains poorly understood why neurodegenerative diseases occur in only a fraction of individuals with a genetic predisposition and conversely, why individuals with no genetic risk of a disorder develop one. Chronic diseases like Alzheimer’s, Parkinson’s, and multiple sclerosis are speculated to result from a combination of genetic and environmental factors, a concept commonly referred to as the “multiple hit hypothesis”. A number of bacterial infections have been linked to increased risk of neurodegeneration, and in some cases, clearance of bacterial pathogens has been correlated with amelioration of CNS deficits. Additionally, mutations in several genes known to contribute to CNS disorders like Parkinson’s Disease have repeatedly been implicated in susceptibility to intracellular bacterial infection. Recent data has begun to demonstrate roles for these genes (Parkin, PINK1, and LRRK2) in modulating innate immune outcomes, suggesting that immune dysregulation may play an even more important role in neurodegeneration than previously appreciated. This review will broadly explore the connections between bacterial infection, immune dysregulation, and central nervous system (CNS) disorders. Understanding this interplay and how bacterial pathogenesis contributes to the “multiple-hit hypothesis” of neurodegeneration will be crucial to develop therapeutics to effectively treat both neurodegeneration and infection.